تــأثير الغـــذاء الطحلبــــــــي في نمــــو وتكاثــــــر القشري Daphnia magna من متفرعات القــــرون (Cladocera–Daphniidae) تحت الشــروط المخبرية - زيني, أديب; عاقل, مي (Latakia University Journal -Biological Sciences Series, 2019)
The Study were conducted on Daphnia magna .which is an aim to culture as live food for larval fish and crustaceans in fish farms. The first batch of these Crustaceans, were collected from then earest fresh water bodies of Tishreen University, Then the individuals have been adapted in the laboratory conditions to preparation them to a series of Experiments. Then we were determination the effects of kind food algae (Chlorella sorokiniana, Scenedesmusobliquus, Anabaena variabilis), in some biological characteristics as growth rate and reproduction rate.Experimentlastedfrom15/11/2018until15/02/2019. The results showed that the suitable food algae to growth and reproduction D.magna is Scenedesmus obliquus, which can use as live food during culture of D.magna in future. تمت الدراسة على أفراد النوع القشريDaphnia magna الذي يعد هدفاً للاستزراع ويستخدم كغذاء حي ليرقات الأسماك والقشريات في المزارع السمكية، حيث تم الحصول على الدفعة الأولى منها من بعض الأوساط المائية العذبة القريبة من جامعة تشرين، وأقلمت في المختبر تمهيداً لإجراء سلسلة من التجارب المخبرية عليها، حدّد فيها تأثير الغذاء الطحلبي Scenedesmus obliquus ;Chlorella sorokiniana ، Anabaena variabilis على بعض الخصائص البيولوجية للنوع كمعدل النمو والتكاثر. استمرت التجربة من 15/11/ 2018 ولغاية 15/2/ 2019م. بّينت النتائج أن النوع الطحلبي المناسب لحياة أفراد هذا النوع هو طحلب Obliquus Scenedesmus، والذي يمكن اعتماده كغذاء حي عند تجارب استزراع D.magna مستقبلاً.